EDUCATION AND UNDERSTANDING (TO THE QUESTION OF APPLICABILITY OF A TECHNOLOGICAL APPROACH IN PEDAGOGY) - Nina I. Lobanova (Высшее образование в России)
The article discusses the context of transition from traditional education paradigm to the technology paradigm and brings up a question of the validity of direct transfer of a technological approach from the production sector into education sphere. The author presents her considerations on the applicability of the technological approach from the point of view of the humanistic (dialogic) tradition. The author arrives to a conclusion that the technological approach inherently denies any subjectivity, any possible act of understanding, and “humanization” of technological approach in the upshot implies pedagogue’s transformation into “communicator”, “engineer”, “technologist”, “manipulator”.